The Effect of Perceived Risk and Expectation Confirmation Model on Purchase Intention Through McDonald’s App - Hidayat, Anas (Archives of Business Research, 2022)
This study aims to analyze the effect of perceived risk and Expectation Confirmation Model (ECM) towards repurchase intention through the McDonald's application. In particular, this study analyzed the effect of performance confirmation, perceived usefulness, perceived risk, satisfaction towards repurchase intention. The research method used is a quantitative approach. The number of samples used in this study are 290 respondents through an online questionnaire. The data analyzed with structural equation modeling (SEM) and processed by AMOS 24.0. The results of the SEM analysis show that perceived confirmation has a positive and significant effect on perceived usefulness and satisfaction. Perceived usefulness has a positive and significant effect on satisfaction. Satisfaction has a positive and significant effect on repurchase intention. Perceived risk has a positive and not significant effect on satisfaction. Also, perceived risk has negative and not significant effect on perceived usefulness and repurchase intention.